Mentorship in Higher Education - Alexandra Zografou; Laura McDermott (GiLE Journal of Skills Development, 2022)
Although mentorship in business settings is typical, its emergence as a tool in education started only recently. Consequently, this new opportunity has initiated a discussion about mentorship and its principal elements in an academic context. Aspects like the mentor profile, the relationship built between mentors and mentees, and the scope of mentorship have been constantly explored and debated by researchers in this field. All contributions are invaluable; however, the information on what the authors consider the fundamental elements of mentorship is scattered throughout many sources. This is precisely what we are attempting to do in this article; by presenting insights from a literary review and investigating the principal aspects of a successful mentorship program in Higher Education, we are answering the most fundamental mentorship-related questions – what mentorship involves; what the qualities of the ideal mentor are; what the student-mentor interaction entails; what the role of the mentor is; and what activities this interaction should include – in a single, well-organized source.